Odpowiedzi

2009-12-10T20:05:29+01:00
A) 2x(3x+5)(4y-6)-2(x+3y) =
= 2x(12xy-18x+20y-30)-2x-6y=24x²y-36x²+40xy-60x-2x-6y=
= 24x²y+40xy-36x²-62x-6y

b)-3(5-3a)-(4b-2c)+¼(a-c)=-15+9a-4b+2c+¼a-¼c=-15+8¾a-4b+1¾c
2009-12-10T20:06:41+01:00
A) szczerze to nie wiem..
b) -15+9a-4b+2c+1/4a-1/4c = 9 i ¼a-4b+1 i 3/4c-15
Najlepsza Odpowiedź!
2009-12-10T20:08:07+01:00
A)2x(3x+5)(4y-6)-2(x+3y)=
2x(12xy-18x+20y-30)-2x-6y=
24x^y-36x^-40xy-60x-2x-6y=
24x^y-36x^-62x-40xy-6y

b)-3(5-3a)-(4b-2c)+¼(a-c)=
-15+9a-4b+2c+¼a-¼c=
9¼a-4b+1 3/4c-15

^ - do potegi 2
3/4 - trzy czwarte( jeden i trzy czwarte <w b>)